2002
DOI: 10.1046/j.1365-2516.2002.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of prophylaxis treatment in children with severe haemophilia

Abstract: The practice of prophylactic treatment of boys with severe haemophilia has been evaluated in our centre. Prophylaxis was started at the median age of 3.7 years (range 0.4-12.7 years) in 38/41 children (93%) under 17 years of age. Median follow-up was 4.1 years (range 0.4-12.7 years). The criteria of primary prophylaxis according to the definition by the European Paediatric Network of Haemophilia Management was fulfilled by 9/38 (24%). Although a majority [76%, 29/38] of the children started prophylaxis after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 17 publications
2
88
0
2
Order By: Relevance
“…After 12–30 months of follow-up, every-other-day prophylaxis was shown to significantly reduce the incidence of joint hemorrhage and the relative risk for joint damage compared with enhanced episodic therapy. While factor consumption was significantly higher in the prophylaxis group, potential savings may be realized from fewer complications and a reduced need for orthopedic surgery [6, 21, 22]. These compelling results, coupled with previous observational studies and case reports [4,5,6,7,8,9,10,11], not only establish prophylaxis as optimal therapy for patients with severe hemophilia A, but argue for its use as standard of care.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…After 12–30 months of follow-up, every-other-day prophylaxis was shown to significantly reduce the incidence of joint hemorrhage and the relative risk for joint damage compared with enhanced episodic therapy. While factor consumption was significantly higher in the prophylaxis group, potential savings may be realized from fewer complications and a reduced need for orthopedic surgery [6, 21, 22]. These compelling results, coupled with previous observational studies and case reports [4,5,6,7,8,9,10,11], not only establish prophylaxis as optimal therapy for patients with severe hemophilia A, but argue for its use as standard of care.…”
Section: Discussionmentioning
confidence: 95%
“…CVAD implantation makes home-administered prophylaxis possible, but safe management of these devices requires close cooperation between families and HTCs. Extensive patient and family education is imperative and should be reinforced on a continuing basis [22]. Caregivers should receive thorough instruction about the use of CVADs and should also be educated about the signs of complications.…”
Section: Discussionmentioning
confidence: 99%
“…1). Other studies have also demonstrated significant improvements in outcomes with the use of prophylactic treatment [3,4,8,[10][11][12][22][23][24].…”
Section: Discussionmentioning
confidence: 98%
“…Dies ist vermutlich darauf zurückzuführen, dass aufgrund medizinischer Fortschritte in der Behandlung dieser Erkrankung inzwischen eine prophylaktische Therapie durchgeführt und auf diese Weise Blutungen vorgebeugt werden kann [29]. Dies wird von den Eltern als sehr entlastend wahrgenommen und geht mit einer deutlichen Verringerung der krankheitsbezogenen Einschränkungen der betroffenen Kinder einher [21,30].…”
Section: Psychosoziale Krankheitsbelastungenunclassified